Pengembangan Bahan Ajar Model Booklet Materi Sumber Daya Hutan Kelas Vii - Utomo, Muhamad Akhyar Wildan, Drs. Suharjo, M.S (2017)
This research aims to know the criteria learning materials and learning materials in the model to know the theme of the potential resources of the forest are conducted at MTs N 2. This research has two goals are (1) find out the desired criteria of learning materials teachers and students on the material potential of forest resources; (2) developing learning materials potential of forest resources of Class VII ; (3) the effectiveness of learning materials. Research, Research and Development (R & D) using the model of the Dick and Carrey. The research was conducted at MTs N 2 Surakarta to retrieve data needs, product trials, and experimental learning materials. Engineering data collection via the question form and test. The results of the research is to produce learning materials Booklet-shaped form of the potential and management of forest resources in accordance with the needs of the students and teachers after being validated by experts and tested. The results of the experiment materials and management potential of forest resources indicates that the results of student learning by using learning materials have an average value of pre test is performed after learning 63.63 using developer book shows the results of the average value of the post test results mean 82.27 pre test experimental group increased 19% from the previous result.